2018
DOI: 10.3390/f9060301
|View full text |Cite
|
Sign up to set email alerts
|

Biotic and Abiotic Drivers of Sap Flux in Mature Green Ash Trees (Fraxinus pennsylvanica) Experiencing Varying Levels of Emerald Ash Borer (Agrilus planipennis) Infestation

Abstract: While the relationship between abiotic drivers of sap flux are well established, the role of biotic disturbances on sap flux remain understudied. The invasion of the emerald ash borer (Agrilus planipennis Fairmaire, EAB) into North America in the 1990s represents a significant threat to ash trees (Fraxinus spp.), which are a substantial component of temperate forests. Serpentine feeding galleries excavated by EAB larvae in the cambial and phloem tissue are linked to rapid tree mortality. To assess how varying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 76 publications
(112 reference statements)
0
12
0
Order By: Relevance
“…The role of other limiting resources may be particularly important for non-ash canopy trees which likely already have access to full sun. Previous ash mortality studies have shown water table rise (Slesak et al 2014), a decrease in sap flux during early of EAB infestation (Flower et al 2018), and significant increases in maple tree radial growth without greater sun exposure each support belowground resource availability increasing with ash mortality. Furthermore, changes in belowground resources were attributed to higher fine root densities within red spruce, Picea rubens, declinecaused gaps (Battles and Fahey 2000).…”
Section: Mechanismmentioning
confidence: 88%
“…The role of other limiting resources may be particularly important for non-ash canopy trees which likely already have access to full sun. Previous ash mortality studies have shown water table rise (Slesak et al 2014), a decrease in sap flux during early of EAB infestation (Flower et al 2018), and significant increases in maple tree radial growth without greater sun exposure each support belowground resource availability increasing with ash mortality. Furthermore, changes in belowground resources were attributed to higher fine root densities within red spruce, Picea rubens, declinecaused gaps (Battles and Fahey 2000).…”
Section: Mechanismmentioning
confidence: 88%
“…The latest research indicated that A. mali could lead to a significant seasonal decrease in chlorophyll fluorescence parameter Fv/Fm (Dr. Zhang Jing, Xinjiang institute of Ecology and Geography, unpublished), which may determine photosynthetic carbon gain, causing the decline in long-term WUE under seasonal droughts. According to the finding of Flower et al [11], ash tree mortality was related to chronic water stress due to the damage of vascular tissues caused by A. planipennis, and an enriched leaf δ 13 C indicated high stomatal resistance and low photosynthetic rate under water stress. Similarly, δ 13 C enrichment in leaf tissues observed in our study indicated the reduction in water availability due to the damage by A. mali.…”
Section: Tree Dieback and Borer-induced Water Stressmentioning
confidence: 97%
“…Understanding the causality between insect infestation and tree mortality is critical to successful pest management and enhancement of forest ecosystem resilience. The health status of individual trees, as well as of the forest ecosystem, was associated with physical stresses caused by pests, including water stress and nutrition deficiency [10][11][12][13][14][15]. Due to restricted water and nutrient use efficiency, as well as altered metabolic dynamics after pest infestation, trees can become more susceptible to subsequent, secondary biotic and abiotic stresses [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Females lay their eggs in crevices of ash bark and, upon hatching, larvae bore into the phloem to feed, creating serpentine galleries in the phloem and outer sapwood. These galleries slow the movement of nutrients and water throughout a tree, girdling the branches and trunk (Flower et al ., ). Girdled branches are nutrient‐starved and do not produce leaves.…”
Section: Introductionmentioning
confidence: 97%